Customer Satisfaction with Mobile Phone Operators: An Exploratory Study in Kuala Lumpur, Malaysia - Bin Dahari, Zainurin; Rahman, Muhammad Sabbir; Ferdous Azam, S. M. (Indian Journal of Marketing, 2011)
Customer satisfaction is a significant issue for most marketers in order to maintain loyalty. Therefore, the mobile phone operators facilitate numerous marketing activities across the nations in order to capture their loyalty. The current research looked into determinants of customer satisfaction in the mobile phone operators in Malaysia. For this reason, a total of about one hundred questionnaires were randomly distributed to customers of a specific area in Malaysia back in 2009. Results indicate that there is a strong relationship among service quality, brand image and price towards customer satisfaction.